Implementation of Management Information Systems in MSMEs Using E-Commerce Platforms - Muhammad Yordan Dafarin Fadil; Aditya Ramadhan; Faisal Hairi (Escalate : Economics and Business Journal, 2026)
The rapid growth of e-commerce in Indonesia, with a digital economy GMV of USD 90 billion in 2024, encourages MSMEs to adopt digital platforms as business channels. However, empirical evidence on whether e-commerce alone improves MSME performance remains mixed, and the role of Management Information Systems (MIS)-particularly accounting information systems-in this relationship is often overlooked. This article examines the contribution of MIS implementation to MSME performance through a literature review of empirically verified national and international sources (2019-2024). Results show that e-commerce's effect on MSME performance is inconsistent across studies-positive but not always significant-while the simultaneous use of accounting information systems together with e-commerce produces a more consistent positive and significant effect on performance. Key challenges include underutilized financial information systems, low cybersecurity awareness, and adoption driven more by external trading-partner pressure than internal strategic initiatives. The article concludes that MIS adoption success depends on technology, organizational readiness, and environmental factors as conceptualized in the Technology-Organization-Environment framework.